A review of sacral nerve stimulation for faecal incontinence following rectal surgery and radiotherapy. (November 2015) - Thomas, G. P.; Bradshaw, E.; Vaizey, C. J.
Abstract Aim Faecal incontinence may occur following rectal surgery and/or radiotherapy for rectal cancer. The aim of this paper was to review the evidence to support the use of sacral nerve stimulation (SNS) for patients with incontinence who had undergone rectal surgery or received rectal radiotherapy. Method A search was performed of PubMed, Medline and Embase. All studies which reported the outcome of SNS in patients who had undergone a rectal resection or radiotherapy were reviewed. Results The first report of SNS following rectal surgery was in 2002. Since then seven further studies have described its effect in patients who have undergone anterior resection or pelvic radiotherapy. The total number of patients was 57. All studies were single group series, which ranged in size from one to 15 patients. The follow‐up ranged from 1 to 36 months. The success of peripheral nerve evaluation ranged from 47% to 100%. Permanent SNS improved the symptoms and in some studies this was reflected in improved quality of life. The wide variation of patient factors, operations performed, the dose of radiotherapy given and time from operation makes interpretation of the results difficult. Conclusion Larger studies with better patient selection are needed to investigate the effect of SNS on incontinence following radiotherapy or rectal surgery.